Die Bybel in die geding: Teks versus dogma - Spies, Lina (HTS teologiese studies, 2004)
The Bible at stake: Text versus dogmaThis article concentrates on one of the great achievements of postmodernism regarding theology: the highlighting of the inseparable relation between religion and poetry. The article argues that, as we are unable to fashion a dependable representation of our world and of God, we have to return to the text and to the language of belief as sole way of expressing our thoughts about God and about belief. The language of belief is not the language of dogma, but that of poetry, and the language of poetry is figurative language. In illustration of this, the text of Samson is reread not as factually-true history, but as the tragic story of a person whose God-given calling and talents are in conflict with his natural drives and gifts, but whose heroic death nevertheless ultimately serves to glorify God. In conclusion the article pleads for the liberation of the Bible from the Greek-Roman construction of it, so that it may again begin to tell stories through which the reader may learn to comprehend something of God. So, too, the Jewishness of Jesus, which has been eroded by dogma and preaching, may be rediscovered.